Effect of Nutrient Management Practices on Growth, Yield and Economics of Vegetable Indian Bean and its Residual Effects on Fodder Pearl Millet under Vegetable Indian Bean–Fodder Pearl Millet Cropping System - Sumanth Kumar, G. V.; Arvadiya, L. K.; Vishwanatha, V. E.; Bartwal, Dhwani; Katara, Akshay R.; Patel, Prerak M.; Teli, Kashinath Gurusiddappa; Kumar, Tamminaina Sunil; Chethan, K. S. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted in vegetable Indian bean (Dolichus lablab L.)–Fodder Pearl millet (Pennisetum glaucum L.) cropping sequence under integrated nutrient management at Navsari Agricultural University, Navsari, Gujarat, India during the rabi seasons (November to February) of 2019–20 and 2020–21 and summer seasons (March to May) of 2020 and 2021. It consisted of six INM treatments applied to vegetable Indian bean during rabi season as main plot treatments replicated four times in randomized block design and during summer season each main plot treatment was splited into three sub-plot treatments with three levels of RDF to fodder pearl millet resulting in eighteen treatment combinations replicated four times in split plot design. The experiment was conducted on the same site without changing the randomization of the treatments for the successive year to assess the residual effects. On the basis of two year pooled results, almost all the growth attributes, yield attributes and yield, net returns and B:C ratio were found significantly superior with the treatment T1 (100% RDN through chemical fertilizer+5 t ha-1 of FYM) in vegetable Indian bean. Similarly, during summer season, the residual effect of INM treatments applied to preceding vegetable Indian bean, the treatment T1 (100% RDN through biocompost) recorded significantly higher growth attributes, yield attributes and yield, net returns and B:C ratio in fodder pearl millet but it remained on par with the treatments T6 and T5. Whereas, direct application of fertilizer levels applied to fodder pearl millet in summer season, the treatment consisting of 100% RDF (F3) recorded significantly higher values of growth, yield, net returns and B:C ratio.